A Water[shed] Moment for Articulating a Professional Practice of Education Resource Creation - Abbey MacDonald; Kim Beasy (Australian Journal of Environmental Education)
Teachers are grappling with increased pressure and expectations to facilitate transformative education experiences, the kinds of experiences that cultivate dispositions and skillsets essential for young peoples’ preparedness to imagine and create sustainable futures. As expectations for teachers grow, so too do initiatives intended to assist their efforts, such as the advent of classroom-ready education resources. The rise of educational resources gives cause for closer examination of how they are developed, particularly with respect to the ways they situate content in the deployment of curricular, methodological and pedagogical concepts. This article presents a practice and process of education resource creation using multi-modal content that entangles global education and conservation agendas. Through the mediating lens of UNESCO’s pillars of education, a critical discussion of the utility of these for enabling and inhibiting the articulation of a professional practice for education resource creation is offered. With the imperative for sustainability-focused education and prevalence of education resources being produced to support this, we scrutinise the importance of demystifying the professional practice of education resource creation. In doing so, we point to insights that become available when the curricular, pedagogical and methodological concepts informing education resource creation are made transparent and accessible.